Analisis Jalur (Path Analysis) DER Terhadap Return Saham - Siti Maisaroh; Imron Mawardi (Universitas Airlangga, 2015)
A source of company funds reflected through foreign capital and their own capital that was worn by the company. Jakarta islamic index is one stock index in indonesia who calculates an average price index stock for a stocks which satisfies the criteria of investment in by islamic syariah. Public companies of JII having financial concerns about the limitation debt, that is debt ratio. This limitation used to review whether there is significant influence of the debt and profitability to return of manufacturing firm in JII. The research approach that used is quantitative analysis by technical lines ( paths analysis ). The exogent variable that used is DER , while the endogent variable is return of stock and the intervening variable is ROE. The result obtained that DER influence significanly to ROE, ROE has no significant influence on Return of stock, and DER has no significant influence on return of stock.